Economic benefit evaluation model of distributed energy storage system considering custom power services - Fang, Jun; Pei, Zhigang; Chen, Tianheng; Peng, Zhihui; Kong, Shiwei; Chen, Jiaming; Huang, Shanhe (Frontiers in Energy Research, 2023)
An economic benefit evaluation model of distributed energy storage considering multi-type custom power services is proposed in this paper. Firstly, the control mode and revenue model of distributed energy storage for reactive power compensation, renewable energy consumption, peak and valley arbitrage are analyzed based on the four-quadrant operation characteristics of energy storage converter. Secondly, an economic benefit evaluation model of custom power services considering the life cycle degradation cost, investment payback period, net present value, and internal return rate of energy storage is formulated. Finally, comparative studies demonstrate the effectiveness and superior performance of the proposed methodology on the economic benefits and practical value. The influence of reserve capacity ratio of energy storage converter, additional price for power quality management, peak-valley price difference, battery cost and project cycle on the annual return and internal rate of return is revealed through the sensitivity analysis, which provides the decision-making reference for battery selection and capacity allocation of distributed energy storage participating in various custom power services.